“Seasoning” Modern Historical Epic with Miracles: the «strani incanti» of Girolamo Graziani’s “Conquisto di Granata” (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
«Un labirinto nel quale si aprono altri labirinti»: the formula that Italo Calvino used to define the poetic universe of Orlando Furioso could be perfectly applied to Girolamo Graziani’s Conquisto di Granata (1650). The historical epic poem dedicated to the relatively recent watershed event of the Reconquista – the conquest of Granada (1492) – absorbed some of the most significant trends and transformations the epic genre underwent in the Seicento, among which the dialectic coexistence of the “marvellous” and the “verisimilar”, as well as the search for novelty and variety and the intrusion of modern history. The essay deals with Graziani’s adoption and re-elaboration of the classical epic topoi belonging to the dimension of the “marvellous”, i.e. the allegorical confrontation of Heaven and Hell, celestial weapons, loci amoeni, enchanting sorceresses, horrible illusory monsters and other magic devices inherited from the chivalric epic tradition. Special attention is given to the interaction of such characteristic epic elements as the providential and the “fantastic” “marvellous” with the dimension of modern history (embodied by the figure of Cristopher Columbus), clearly perceived in the intricate world of Graziani’s poem that similarly to the ariostesque epic, reveals to be a «universo a sé in cui si può viaggiare in lungo e in largo, entrare, uscire, perdercisi».
Keywords: marvellous; verisimilar; history; Conquest of Granada; Christopher Columbus; Girolamo Graziani